2003
DOI: 10.3390/md101027
|View full text |Cite
|
Sign up to set email alerts
|

Rigidin E, a New Pyrrolopyrimidine Alkaloid from a Papua New Guinea Tunicate Eudistoma Species

Abstract: A new pyrrolopyrimidine alkaloid, rigidin E (1) and the known metabolites rigidin (2) and 1-methylherbipoline (3) have been isolated from a Papua New Guinea tunicate Eudistoma sp. A combination of spectroscopic data were used to determine the structures of these metabolites

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…When the two agents were compared as inhibitors of the binding of [3H]colchicine to tubulin,12 however, combretastatin A-4 was more potent than compound 7. In reaction mixtures containing 1.0 μM tubulin and 5.0 μM inhibitor and colchicine, combretastatin A-4 inhibited colchicine binding by 98 ± 0.5 (SD) %, while the result obtained with 7 was 76 ± 0.2%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the two agents were compared as inhibitors of the binding of [3H]colchicine to tubulin,12 however, combretastatin A-4 was more potent than compound 7. In reaction mixtures containing 1.0 μM tubulin and 5.0 μM inhibitor and colchicine, combretastatin A-4 inhibited colchicine binding by 98 ± 0.5 (SD) %, while the result obtained with 7 was 76 ± 0.2%.…”
Section: Resultsmentioning
confidence: 99%
“…rigida found near Okinawa and New Guinea. 3 Recently, we reported a general total synthesis of rigidins A, B, C, and D, which involved only four steps from commercially available starting materials and was amenable to the production of synthetic rigidin analogues. 4 Subsequently, extensive structure–activity relationship studies revealed that the replacement of the 7-deazaxanthine scaffold associated with the rigidins by the 7-deazahypoxanthine variant through the removal of the carbonyl at C2 (Figure 1A) led to compounds possessing significant antiproliferative activities by targeting the microtubule network in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…rigida found near Okinawa and New Guinea and has remained scantly explored despite initial reports of promising biological activities. 10-12 The first general total synthesis of rigidins A, B, C and D, which involved only four steps from commercially available materials, was reported by the authors in 2011 13 and allowed for a thorough investigation of their biological properties. However, despite the earlier reports of promising antiproliferative activity against murine leukemia L1210 cells, 11 the rigidins were found to have very little, if any, activity against cultured human cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…badium [42]. (IC 50 of 100 μg/mL against HCT 116 human colon carcinoma cell lines) [44]. However, the IC 50 of column fraction PI-8 was potent when compared to the lamellarin b from ascidian Didemnum sp.…”
Section: Fig (8) Change In Morphological Features Of the Hela Cellsmentioning
confidence: 98%